ANALISIS PRIORITAS PENGADAAN OBAT MENGGUNAKAN METODE AHP DALAM MANAJEMEN LOGISTIK DI APOTIK ENDAR FARMA - Wibowo, Sadiq Ardo; Hernando, Luki; Rahman, Taufiq; Anugrah, Jelita Balqis; Siswono, Anggi (Universitas Putera Batam, 2025)
This study aims to design a decision support system in determining drug procurement priorities at Endar Farma Pharmacy using the Analytical Hierarchy Process (AHP) method. This method was chosen because of its ability to break down complex problems into a hierarchical structure consisting of objectives, criteria, and alternatives. Data collection was carried out through observation, interviews, documentation studies, and pairwise comparison questionnaires. The five main criteria used in the analysis were the level of drug demand (weight: 0.485), profit (0.227), order lead time (0.089), expiration risk (0.057), and stock availability (0.143). Meanwhile, the alternative drugs evaluated included Paracetamol, Amoxicillin, Metformin, Omeprazole, and Ibuprofen. The results of the AHP synthesis showed that Amoxicillin obtained the highest priority score of 0.295, followed by Paracetamol (0.291), Omeprazole (0.290), Ibuprofen (0.271), and Metformin (0.188). The entire calculation process meets the consistency ratio (CR) < 0.1, indicating that the assessment results are consistent and reliable. The application of the AHP method in this decision support system has been proven to be able to produce more objective and structured recommendations, increase the efficiency of drug logistics management, and help pharmacies reduce the risk of excess and shortage of inventory.